2020
DOI: 10.1186/s12864-020-07104-w
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an 11-microRNA-based signature and a prognostic nomogram to predict the overall survival of head and neck squamous cell carcinoma patients

Abstract: Background Head and neck squamous cell carcinoma (HNSCC) is a fatal malignancy owing to the lack of effective tools to predict overall survival (OS). MicroRNAs (miRNAs) play an important role in HNSCC occurrence, development, invasion and metastasis, significantly affecting the OS of patients. Thus, the construction of miRNA-based risk signatures and nomograms is desirable to predict the OS of patients with HNSCC. Accordingly, in the present study, miRNA sequencing data of 71 HNSCC and 13 normal samples downlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Every year, there are over 655,000 new HNSCC cases (globally), resulting in 90,000 deaths 2 . Tobacco smoking, alcohol consumption and human papillomavirus (HPV) infection are important risk factors for developing HNSCC 3 . Moreover, Epstein-Barr virus (EBV) is strongly associated with nasopharyngeal carcinoma (NPC) 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Every year, there are over 655,000 new HNSCC cases (globally), resulting in 90,000 deaths 2 . Tobacco smoking, alcohol consumption and human papillomavirus (HPV) infection are important risk factors for developing HNSCC 3 . Moreover, Epstein-Barr virus (EBV) is strongly associated with nasopharyngeal carcinoma (NPC) 4 .…”
Section: Introductionmentioning
confidence: 99%
“…With major advances in bioinformatics, proteomics, and techniques of gene analysis, a great deal of researchers has contributed themselves to developing signatures using different methods for predicting the prognosis of patients with head and neck cancer. Prognostic signatures have been developed using miRNA [28,29], alternative splicing [30], immune function molecules [31], and a signature according to m 6 A RNA methylation regulators [32].…”
Section: Discussionmentioning
confidence: 99%
“…Some research shows that miRNA expression profile in solid tumors is significantly altered from that of healthy tissue [8]. Since miRNAs are stably expressed in human tissues and are linked with the initiation and progression of cancer, they could serve as biomarkers for diagnosis, prediction of response to therapy and treatment outcome [9]. Research on HNSCC indicated that many miRNAs are differentially expressed in cancer tissue, with some classified as oncogenic, and others as tumor suppressors [10].…”
Section: Introductionmentioning
confidence: 99%
“…Since miRNAs play a crucial role in cancer development, many studies have investigated the application of miRNA expression analysis as a prognostic tool for HNSCC. Recently published data showed that expression of miRNAs in healthy and tumor tissue of oral squamous cell carcinoma can be associated with patient prognosis, and could be used to predict recurrence and patient survival [9,12]. Several studies demonstrated that expression of miRNAs in patients' serum could be used as a factor predicting patients' survival, disease progression, or risk of developing side effects [13][14][15].…”
Section: Introductionmentioning
confidence: 99%